Minimally invasive lobectomy for early stage non-small cell lung cancer—it can be done without sacrificing oncologic outcomes - Berry, Mark F. (Journal of Thoracic Disease, 2016)
The introduction of minimally invasive surgical techniques to perform lobectomy for non-small cell lung cancer (NSCLC) has significantly changed the practice of general thoracic surgery over the past two decades. Since the first reports of the use of video-assisted thoracic surgery (VATS) to perform lobectomy for NSCLC in the early 1990s (1), many more studies across a wide array of cohorts have reported on short-term and long-term outcomes. Initial studies focused on the feasibility and reproducibility of the procedure (2), and then subsequent studies demonstrated VATS lobectomy had less morbidity compared to thoracotomy (3). Over time, studies have shown that a minimally invasive approach may be particularly beneficial in those patients with higher peri-operative risk due to advanced age or poor pulmonary function (4,5). More recently, experience with robotic-assisted lobectomy has been increasingly reported and a robotic approach appears to provide similar advantages over thoracotomy as a VATS approach (6). Despite these demonstrated benefits, universal adoption of minimally invasive lobectomy for early-stage NSCLC has not occurred (4,7,8).